Caddis flies (Trichoptera) in springs of the nature reserve Struga Dobieszkowska - Majecki, Janusz; Majecka, Katarzyna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
Nine caddis fly species occur in springs and streams of the nature reserve StrugaDobieszkowska. Their life cycle and microdistribution were investigated. Five new species forthe Łódź Upland were found.